PENGENALAN KELAS VIRTUAL UNTUK SANTRI DAN GURU YAYASAN CAHAYA ISLAM MUTIARA IMANI (CIMI) PONDOK BENDA PAMULANG - Sri Rama Putri; Adam Muiz; Dede Sunandar (Abdi Jurnal Publikasi, 2024)
Technology requires us to continue to adapt to current advances and changes. One of the developments and changes that is developing is in the world of education, where learning and teaching activities which are usually carried out between teachers and students meet and interact directly, in other words, teachers to students, students and other students, are not at all connected to the internet network. . But with technology, it is possible to do all these activities, interact and communicate anytime and anywhere without being limited by space and time. To improve effective learning outcomes and continue to strive for this, one way is to enrich knowledge or expand students' knowledge by utilizing information technology, namely virtual classes. Virtual classes are classes that are held without direct face-to-face contact between the teacher and those receiving the teaching materials. Virtual classes are directly connected to the internet. Community Service carried out by a team of Informatics Engineering lecturers at Pamulang University, South Tangerang, chose the Cahaya Islam Mutiara Imani Foundation (CIMI) Pondok Benda Pamulang, South Tangerang as the venue for the implementation. This service activity aims to introduce virtual classroom technology as a support for effective and time-appropriate teaching and learning activities to teachers and students of the Cahaya Islam Mutiara Imani Foundation (CIMI) Pondok Benda Pamulang South Tangerang, with the hope that the learning system can be carried out anytime and anywhere without limitations. given time and space, it is not boring and teachers also have the opportunity to learn and upgrade their broader knowledge. The targeted output of this Community Service is in the form of a national journal with ISSN.